Measurement of phase and amplitude modulations in Sb-Based Films - Avila, L. F.; Nalin, M. [UNESP]; Cescato, Lucila (SPIE, the international society for optics and photonics, 2009)
In this work we studied the changes of the optical constants of films in the binary system Sb2O3-Sb2S3 induced by light in the VIS-UV. The measurements were performed before and after homogeneous irradiation of the films to a Hg lamp and in real time during the holographic exposure of the samples (at 458nm). Changes of the absorption coefficient (amplitude grating) and refractive index (phase grating) were measured simultaneously using the self-diffraction using the holographic setup. Besides the films presented a strong photodarkening effect under homogeneous irradiation, the samples holographically exposed presented only refractive index modulations. None amplitude modulation was measured in real time for spatial frequencies of about 1000 l/mm. © 2009 SPIE.
Keywords: Diffraction; Holography; Photosensitive glasses; Absorption coefficients; Amplitude gratings; Before and after; Binary systems; Phase grating; Photo darkening effects; Real time; Refractive index modulation; Self-diffraction; Spatial frequency; Amplitude modulation; Holographic interferometry; Irradiation; Light refraction; Light sensitive materials; Mercury (metal); Optical constants; Photosensitive glass; Photosensitivity; Refractive index; Refractometers; Thin films; Light